The effect of metabolic risk factors on urinary stone composition: An observational study. Issue 28 (15th July 2022) - Kim, Jae Yoon; Yu, Ji Hyeong; Kang, Seok Ho; Lee, Jeong Gu; Cheon, Jun; Kang, Sung Gu
Abstract : To investigate how the risk factors of metabolic diseases affect urinary stone composition, particularly uric acid (UA) stones. Overall, 583 patients with data on urinary stone composition were retrospectively analyzed and classified into UA and nonUA stone formers according to the presence of the UA component. Various factors were compared between both groups. Participants were categorized according to age, glucose level, HbA1c level, and estimated glomerular filtration rate (eGFR) into subgroups, and the incidence of UA stone was compared. Overall, 137 UA stone formers (23.5%) and 446 nonUA stone formers (76.5%) were included. Mean age and male-to-female ratio were higher in the UA group than in the nonUA group. The rates of diabetes mellitus (DM), hypertension, chronic kidney disease, and coronary artery disease, all of which were associated with differences in urinary stone composition, were higher in the UA group than in the nonUA group. The UA group exhibited lower mean eGFR and higher glucose and HbA1c levels. Similarly, the UA group had higher mean UA levels and predictably lower urinary pH. In subgroup analysis, higher age, glucose level, HbA1c level, and lower eGFR were associated with an increased risk of UA stone formation. In the multivariate logistic regression analysis, the UA group showed a significantly higher age ( P < .001), DM frequency ( P = .049), and HbA1c level ( P = .032), but significantly lower eGFR than the nonUA group ( P < .001). Age and DM were independent risk factors for UA urolithiasis, implying a relationship between urinary stone composition and metabolic diseases. Additionally, renal function and HbA1c level were risk factors for UA stones.